OCT Based Interpretation of the Optic Nerve Head Anatomy and Prevalence of Optic Disc Drusen in Patients with Idiopathic Intracranial Hypertension (IIH) - Elisabeth Arnberg Wibroe; Lasse Malmqvist; Steffen Hamann (Life, 2021)
We aimed to systematically examine the optic nerve head anatomy in patients with idiopathic intracranial hypertension (IIH) using a standardized optical coherence tomography (OCT) protocol. The study retrospectively included 32 patients diagnosed from 2014 to 2021 with IIH. Using OCT, in accordance with a standardized scanning protocol for patients with optic disc drusen, the presence of optic disc drusen, prelaminar hyperreflective lines, peripapillary hyperreflective ovoid mass-like structures, the retinal nerve fiber layer thickness, and macular ganglion cell layer volume was obtained. Optic disc drusen were found in 3.1%, hyperreflective lines in 31.3%, and peripapillary hyperreflective ovoid mass-like structures in 81.3% of all IIH patients at least three months after the time of diagnosis. We found no significant differences in retinal nerve fiber layer thickness or macular ganglion cell layer volume in patients with hyperreflective lines or PHOMS respectively compared to patients without hyperreflective lines (p = 0.1285 and p = 0.1835). In conclusion, the prevalence of optic disc drusen in IIH patients is similar to the reported prevalence in the general population. The high prevalence of hyperreflective lines and peripapillary hyperreflective ovoid mass-like structures in IIH patients suggest these structures be a result of crowding in the optic nerve head caused by papilledema.